2010
DOI: 10.2208/kaigan.66.401
|View full text |Cite
|
Sign up to set email alerts
|

Continuation or Decline of Disaster Management Education Effect with Earthquake and Tsunami Themes

Abstract: Three issues on effects of disaster management education for children in schools are discussed. They are (i) effective disaster management education for young people, (ii) quantification of the educational effects by the questionnaire surveys, (iii) effectiveness and durability of the disaster management education. Date taken for five schools, a high school, two junior high schools, and two elementary schools are examined. The results show that (1) it is important that school teachers and engineers examine dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, these experiments have not been able to analyze the views of people who are unaware and do not attend workshops. Kurosaki et al 4) implemented disaster prevention education for elementary, middle, and high school students through school education program. Their results showed that communication is effective for disaster prevention education, and that disaster prevention awareness decreased after more than one year.…”
Section: Introductionmentioning
confidence: 99%
“…However, these experiments have not been able to analyze the views of people who are unaware and do not attend workshops. Kurosaki et al 4) implemented disaster prevention education for elementary, middle, and high school students through school education program. Their results showed that communication is effective for disaster prevention education, and that disaster prevention awareness decreased after more than one year.…”
Section: Introductionmentioning
confidence: 99%